A STUDY OF THE SOCIO-ECONOMIC PERSPECTIVE OF THE DIGITAL DIVIDE AMONG UNIVERSITY STUDENTS - Bala, Vijaya; Pandey, Govind Ji (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Indians living in the 21st century are known as one of the world's most dynamic, developing, and digitally loving people. With the rapid growth of Digital Technology, the Internet emerged as an important medium for exchanging ideas, opinions and knowledge. The ICT (Information and Communication Technology) facilities are the basic right of every individual for the economic and social exchange of knowledge. The term ‘Digital divide’ denotes the gap between people who have access to modern information and communications technology (ICT), and those who lack it. Various studies and reports suggest that the digital divide is still very much a reality today. The India Inequality Report 2022: Digital Divide by Oxfam underscored that only 38 per cent of households in the country are digitally literate. This report also highlights the rural-urban digital divide in the country. Factors such as educational and income levels, geographical restrictions, lack of motivation, digital illiteracy, discrimination, etc. contribute to the digital divide. This research paper aims to study the socio-economic reasons for digital divide among students of Higher Education. The purpose is to provide a comprehensive analysis of digital technology usage patterns among the students of Higher Education. It also tries to highlight the basic reasons for the digital divide among students. The study exposes the different factors including socio-economic status, geographical status and educational background of the population. The researcher conducted survey among the students of Higher Education and found that the use and access of digital technologies are quite dismal in various caste, class and peri-urban students. The researcher also focused on the ease of access to technology and education. It was quite interesting to see that the students who were from convent education had more knowledge about digital technology than those who came from Hindi medium schools. The Caste, Class, and Place of living also affect the access to digital technology. The difference between have and have not is affecting educational achievements. If we want to make India a digitally literate society then we have to take measures to fill this gap as soon as possible. The government can take various steps like increasing affordability, strengthening internet infrastructure, addressing gender gaps, etc. to tackle the challenge of the digital divide among university students. The findings of the research can be utilized by policymakers to invest in digital education for holistically tackling the digital divide. For example, the research highlights the importance of mobile as a personal device among university students and hence, policies emphasizing boosting the affordability and accessibility of mobile can help boost digital literacy.